Influence of the storage period of eggs from free-range hens on incubation variables (Research, Society and Development, 2020)
The present study aimed at evaluating the different storage periods of eggs from free-range hens on incubation variables. Treatments were composed according to the following egg storage periods: 1 to 5 days, 6 to 10 days, 11 to 15 days and 16 to 20 days. The variables analyzed were egg weight loss, embryonic mortality, hatchability rate and chick weight at birth. The experimental design was completely randomized. The variables related to weight were subjected to analysis of variance and the Scott-Knott test at 5% probability. Egg weight and chick weight at birth were not influenced by egg storage time; however, egg weight loss during storage was greater (P